Effect of Montmorillonite Nanogel Composite Fillers on the Protection Performance of Epoxy Coatings on Steel Pipelines - Atta, Ayman M. (Molecules, 2017)
Montmorillonite (MMT) clay mineral is widely used as filler for several organic coatings. Its activity is increased by exfoliation via chemical modification to produce nanomaterials. In the present work, the modification of MMT to form nanogel composites is proposed to increase the dispersion of MMT into epoxy matrices used to fill cracks and holes produced by the curing exotherms of epoxy resins. The dispersion of MMT in epoxy improved both the mechanical and anti-corrosion performance of epoxy coatings in aggressive marine environments. In this respect, the MMT surfaces were chemically modified with different types of 2-acrylamido-2-methyl propane sulfonic acid (AMPS) nanogels using a surfactant-free dispersion polymerization technique. The effect of the chemical structure, nanogel content and the interaction with MMT surfaces on the surface morphology, surface charges and dispersion in the epoxy matrix were investigated for use as nano-filler for epoxy coatings. The modified MMT nanogel epoxy composites showed excellent resistance to mechanical damage and salt spray resistance up to 1000 h. The interaction of MMT nanogel composites with the epoxy matrix and good response of AMPS nanogel to sea water improve their ability to act as self-healing materials for epoxy coatings for steel.